(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
The position paper on Artificial Intelligence (AI) and Educational Management Information System (EMIS) addresses the pivotal role of AI in transforming educational management practices. It advocates for the responsible integration of AI technologies within EMIS to enhance efficiency, decision-making processes, and student learning outcomes. The paper highlights the potential benefits of AI in EMIS, such as improved data analysis, personalized learning experiences, and administrative automation. Additionally, it acknowledges and addresses ethical considerations, privacy concerns, and potential biases associated with AI implementation. The paper concludes with recommendations for stakeholders to adopt strategies for responsible AI integration, policy development, and areas for further research to maximize the positive impact of AI on educational management.